The The Therapeutic Effects of Autologous Platelet-Rich Plasma Gel on Cutaneous Wound Healing in Rescued Horses: The Effects of Autologous Platelet-Rich Plasma Gel on skin Wound Healing in Horses - Sajjad, MT; Akbar, H; Khan, MA; Mushtaq, MH; Bokhari, SG; Hayat, MA; Mustafa, G (Journal of the Hellenic Veterinary Medical Society, 2023)
This study explored the effect of platelet-rich plasma gel on skin wound healing in rescued horses. A total of twenty horses were used and allocated into two groups: PRP-treated Group A (n=10) and ASD-treated Group B (n=10). Group A animals were treated with autologous PRP gel, while group B animals were treated with sterile saline. A full-thickness (1.5 mm2) skin wounds were selected in each horse. Histopathological examination of wound tissue in horses was performed on days 8, 40, and 60. Wound epithelialization was assessed by HE staining, and collagen re-establishment was assessed by Masson’s trichrome staining. The CAT activity and MDA concentration were assessed in blood samples on days 8, 40, and 60. All data were subjected to statistical analysis. We observed a highly significant increase (P<0.01) in re-epithelization at days 40 to 60 in the PRP wounds compared to the ASD wounds. Collagen was well organized (P<0.01) in the PRP wounds compared with the ASD wounds at day 40 to day 60. MDA concentration was significantly decreased from day 40 to day 60 (P<0.05) in the PRP wounds than the ASD wounds. CAT activity showed no difference (P>0.05) between PRP wounds and ASD wounds. In conclusion, compared to ASD wounds, PRP wounds promoted cutaneous wound healing in horses by suppressing oxidative stress levels, accelerating wound epithelialization, and generating organized tissue, interlocking collagen bundles of dermal collagen. However, ultrasonographical assessment level study is needed to further investigate the effect of PRP gel on skin wound healing in rescued horses. Keywords: Horses, Oxidative stress, Platelet-Rich Plasma, Sterile saline, Skin Wound Healing.